Interacting binaries and extrasolar planets: Challenges for VLTI - Gazeas, K. D. (EAS Publications Series, 2003)
Optical Interferometry can play an important role in modern astronomy. Extrasolar planet and binary star research, are some of the fields, where we will face important discoveries in the future. For the VLTI this will be a real challenge, since it will be the pioneer in angular resolution. In addition, high flux sensitivity will help detecting not only Jupiter-sized planets, but Earth-sized planets too. The ability of the VLTI in detecting new planets, measuring stellar diameters and stellar proper motions, with the use of such techniques, is presented.